The interactions of k with complex nuclei in the energy range (100–800) MeV: II. The interaction lengths and elastic scattering of 750 MeV π -mesons in G5 emulsion - Allen, J. E.; Apostolaris, A. J.; Lee, Y. V.; Major, J. V.; Perez Ferreria, Emma (Taylos & Francis, 1961)
Fil: Allen, J. E. University of Durham; Reino Unido